High acyl gellan as an emulsion stabilizer. (30th March 2016) - Vilela, Joice Aline Pires; Cunha, Rosiane Lopes da
Highlights: High acyl (HA) gellan was able to stabilize coarse oil-in-water emulsions. Emulsion stabilization was related to high viscosity of HA gellan aqueous dispersion. HA gellan aggregates formed in aqueous phase were a critical factor in emulsions formation. Low acyl gellan was not capable of stabilizing emulsions in the same conditions as that of HA gellan. Abstract: High acyl gellan (0.01–0.2% w/w) was used as stabilizer in oil in water emulsions containing 30% (w/w) of sunflower oil and prepared under different process conditions. Stable emulsions to phase separation could be obtained using high acyl gellan (HA) content above 0.05% (w/w), while low acyl gellan (LA) prepared at the same conditions could not stabilize emulsions. Emulsions properties depended on the process used to mix the oil and gellan dispersion since high pressure homogenization favored stabilization while very high energy density applied by ultrasound led to systems destabilization. Emulsions prepared using high pressure homogenization showed zeta potential values ranging from −50 up to −59 mV, suggesting that electrostatic repulsion could be contributing to the systems stability. Rheological properties of continuous phase were also responsible for emulsions stabilization, since HA gellan dispersions showed high viscosity and gel-like behavior. The high viscosity of the continuous phase could be associated to the presence of high acyl gellan microgels/aggregates. Disentanglement of these aggregates performed by ultrasound strongly decreased the viscosity and consequently affected the emulsions behavior, reducing the stability to phase separation.